2013
DOI: 10.1523/jneurosci.4015-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Multifocal Attentional Enhancement of Stimulus Processing in Early Visual Areas Predicts Tracking Performance

Abstract: Keeping track of multiple moving objects is an essential ability of visual perception. However, the mechanisms underlying this ability are not well understood. We instructed human observers to track five or seven independent randomly moving target objects amid identical nontargets and recorded steady-state visual evoked potentials (SSVEPs) elicited by these stimuli. Visual processing of moving targets, as assessed by SSVEP amplitudes, was continuously facilitated relative to the processing of identical but irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 36 publications
2
62
1
Order By: Relevance
“…Given that we found no decline in performance with increasing number of attention foci as measured by accuracy and false alarm rate and only a small decline in reaction time (of a magnitude much smaller than would be predicted by serial monitoring) our results, consistent with previous studies910, lend further behavioural support for parallel rather than serial monitoring of multiple foci.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that we found no decline in performance with increasing number of attention foci as measured by accuracy and false alarm rate and only a small decline in reaction time (of a magnitude much smaller than would be predicted by serial monitoring) our results, consistent with previous studies910, lend further behavioural support for parallel rather than serial monitoring of multiple foci.…”
Section: Discussionsupporting
confidence: 90%
“…This impression is supported by behavioural studies demonstrating the capacity to selectively attend to multiple non-contiguous locations and delimited objects3456. Neurophysiological evidence has confirmed these findings showing enhanced neural activation for spatially discrete attended targets in comparison to intervening spatial regions or distractors78910. However, little is known about how the brain controls the movements of the eyes during such complex attentional allocation.…”
mentioning
confidence: 89%
“…Indeed, both FEF and LIP have been causally linked to visual performance in covert attention tasks (Moore andFallah 2001, 2004;Wardak et al 2004Wardak et al , 2006Balan and Gottlieb 2009), and FEF activity is known to drive increases in firing rates in visual cortex, mimicking the consequences of selective attention Armstrong et al 2006;Armstrong and Moore 2007). Whereas no study has explored predictive shifts of covert attention in early visual areas, recent single-cell recordings in monkeys (Niebergall et al 2011) and event-related potentials in humans (Drew et al 2009;Doran and Hoffman 2010;Störmer et al 2013) have shown that visual responses in striate and extrastriate cortical areas show enhanced responses to tracked compared with untracked objects. Finally, during smooth pursuit, visual performance is highest at the current position of the target (Lovejoy et al 2009) or even ahead of it (van Donkelaar and Drew 2002; Khan et al 2010), both of which require predictive shifts of attention to compensate for the neural delays of the visuomotor system.…”
Section: Discussionmentioning
confidence: 99%
“…Common practice recommends a normalization of individual absolute SSVEP amplitudes Störmer et al, 2013;Andersen, Fuchs, & Müller, 2011). This normalization serves two main purposes: It strips amplitudes of their large interindividual variance while retaining the net effect of SSVEP modulation by some experimental factor (here, spatial attention).…”
Section: Gain Effects On Ssvep Amplitudementioning
confidence: 99%
“…Critically, SSVEP amplitudes can be modulated by attention (Müller, Picton, et al, 1998;Morgan, Hansen, & Hillyard, 1996) as well as interstimulus competition (Keitel, Andersen, & Müller, 2010;Fuchs et al, 2008). Previous experiments have exploited these characteristics to study modulations of visual processing under conditions of multifocal attention (Itthipuripat, Garcia, & Serences, 2013;Störmer, Winther, Li, & Andersen, 2013;Müller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%